Arca Durga Mahisasuramardini: Unveiling The Beauty and Myths Behind The Siwa Temple at Prambanan - Muhamad Thaariq Maulana; Husni Ijas; Yohannes Mukti Wibowo (Journal of Social Research, 2025)
This article specifically discusses the Durga Mahisasuramardini statue, from its physical details to its connection with Roro Jonggrang in the interpretation of the community. The research methods used in this article are observation and literature study. Prambanan Temple is one of the largest Hindu temples ever built in Java. The temple was built in 850 AD by King Pikatan and perfected by King Lokapala and King Balitung Maha Sambu. Prambanan Temple is also often known as Roro Jonggrang Temple, which comes from the folk tale between Princess Roro Jonggrang and Bandung Bondowoso. Prambanan Temple has three main temples: Brahma Temple, Shiva Temple, and Vishnu Temple. Previous research has only discussed Prambanan Temple and the legend of Roro Jonggrang in the community's belief, but no research has specifically discussed the Durga Mahisasuramardini statue in Prambanan Temple and its connection to Roro Jonggrang. In this research, the focus is on the Shiva Temple, especially the Durga Mahisasuramardini statue in the north chamber of the temple. This Durga statue has interesting details, from the structure and patterns to the ornaments around it. In addition, there is also the story of Roro Jonggrang associated with this Durga statue.